2009
DOI: 10.1177/2156759x0901200401
|View full text |Cite
|
Sign up to set email alerts
|

Who Sees the School Counselor for College Information? A National Study

Abstract: Using the 2002 Educational Longitudinal Study database, a national survey conducted by the National Center of Education Statistics, the authors investigated the characteristics of students who seek out professional school counselors in order to receive college information. Results indicated that African Americans and female students were more likely to contact the school counselor for college information. In addition, students in high-poverty, large schools and schools with smaller numbers of counselors were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 6 publications
6
67
0
Order By: Relevance
“…Finally, the mean self‐efficacy for participants in schools with enrollments of over 1,000 students was higher than the mean for those in schools with enrollments between 501 and 1,000. This outcome is surprising because Bryan, Holcomb‐McCoy, Moore‐Thomas, and Day‐Vines (2009) found that students who attended smaller schools reported being more likely to meet with their school counselor to receive information about college. The discrepancy in findings may be due to the fact that although students may seek out their school counselors for career and college advising services, their school counselors may or may not have adequate self‐efficacy to provide those services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the mean self‐efficacy for participants in schools with enrollments of over 1,000 students was higher than the mean for those in schools with enrollments between 501 and 1,000. This outcome is surprising because Bryan, Holcomb‐McCoy, Moore‐Thomas, and Day‐Vines (2009) found that students who attended smaller schools reported being more likely to meet with their school counselor to receive information about college. The discrepancy in findings may be due to the fact that although students may seek out their school counselors for career and college advising services, their school counselors may or may not have adequate self‐efficacy to provide those services.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, students will experience positive outcomes if school counselors provide assistance with applications for admission to postsecondary education institutions. Moreover, Bryan et al (2009) reported significant differences between students who sought out their school counselors for college information and those who did not. In turn, our study may offer important insight about what factors might influence school counselors’ self‐efficacy in providing these services.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the popularity of the NCES national longitudinal databases for research use in education-related disciplines, few school counseling researchers (Adams, Benshoff, & Harrington, 2007;Bryan, Holcomb-McCoy, Moore-Thomas, & Day-Vines, 2009;Lee & Smith-Adcock, 2005;Trusty & Niles, 2003) have used these databases to investigate student outcomes or implications of school counseling practice. Furthermore, every year since 1990, with the support of the National Science Foundation (NSF), the American Educational Research Association (AERA) Grants Program has awarded a number of dissertation grants and research grants to doctoral-level and faculty researchers specifically for research using large-scale national and international databases maintained by NCES and the NSF (Murdock, 2006(Murdock, , 2008Whiteley, Seelig, Weinshenker, & Schneider, 2002).…”
Section: Research Use Of the National Longitudinal Data Setsmentioning
confidence: 99%
“…Consequently, African American males lag behind their counterparts in academic achievement (Baker, 2005;Noguera, 2003). Further, the gap between African American males and females with regard to college enrollment, is the largest of all racial groups, with African American males significantly lagging (Bryan, Holcomb-McCoy, Moore-Thomas, & Day-Vines, 2009). The disengagement of African American males from education often occurs by the time they are in 4th grade (Noguera, 2003).…”
Section: African American Malesmentioning
confidence: 99%